2020
DOI: 10.1096/fj.202001515r
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A inhibitor proteins (PKIs) divert GPCR‐Gαs‐cAMP signaling toward EPAC and ERK activation and are involved in tumor growth

Abstract: The PKA‐inhibitor (PKI) family members PKIα, PKIβ, and PKIγ bind with high affinity to PKA and block its kinase activity, modulating the extent, and duration of PKA‐mediated signaling events. While PKA is a well‐known regulator of physiological and oncogenic events, the role of PKI proteins in these pathways has remained elusive. Here, by measuring activation of the MAPK pathway downstream of GPCR‐Gαs‐cAMP signaling, we show that the expression levels of PKI proteins can alter the balance of activation of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…In line with these reports, our transcriptomic analyses of PGE1-treated URECs identified several cAMP regulators, in particular the cAMP-Dependent Protein Kinase Inhibitor Alpha, PKIα (42). The upregulated expression of PKIA in the absence of NPHP1 is expected to lead to decreased activity of PKA, which would be counterbalanced by activation of EP2 and EP4 receptors upon PGE1 treatment through the inhibition of PKIα and increased cAMP production.…”
Section: Ciliogenesis and Campsupporting
confidence: 82%
“…In line with these reports, our transcriptomic analyses of PGE1-treated URECs identified several cAMP regulators, in particular the cAMP-Dependent Protein Kinase Inhibitor Alpha, PKIα (42). The upregulated expression of PKIA in the absence of NPHP1 is expected to lead to decreased activity of PKA, which would be counterbalanced by activation of EP2 and EP4 receptors upon PGE1 treatment through the inhibition of PKIα and increased cAMP production.…”
Section: Ciliogenesis and Campsupporting
confidence: 82%
“…As recently reported in vitro by Hoy et al (2020), PKIA regulates mitogen activated protein kinase (MAPK) and exchange factor directly activated by cAMP1 (EPAC) signaling. [ 32 ] In CRC context, the TCGA‐COAD data displayed that PKIA promoter was found hypermethylated in CRC tumor (and consequent decreased gene expression). However, a study found that PKIA expression was increased in CRC and cancer stem cell samples, as compared to normal colon or stem cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of cervical cancer research, PKIA is considered an important marker for stage III cervical cancer (Banerjee & Karunagaran, 2019). Hoy et al (2020) found that the amplification of PKIA is common in prostate cancer and was associated with reduced progression-free survival. Depletion of PKIA in prostate cancer cells results in reduced migration, increased sensitivity to nest loss apoptosis, and reduced tumor growth.…”
Section: Disscussionmentioning
confidence: 99%
“…Depletion of PKIA in prostate cancer cells results in reduced migration, increased sensitivity to nest loss apoptosis, and reduced tumor growth. By altering the activity of protein kinase A, protein kinase I can act as a molecular switch that drives the gPCR-GMAP1 s-cAMP signal toward activation of α-RAP1 and MAPK, ultimately regulating tumor growth ( Hoy et al, 2020 ). As a transcription factor, ZNF831 (Zinc Finger Protein 831) is thought to regulate the immune response network with phenotypes in breast cancer ( Da Silveira et al, 2017 ).…”
Section: Disscussionmentioning
confidence: 99%